Syed Muhammad Naquib al-Attasâ Semantic Reading of Islam as Din - Widodo, Aris (Al-Jamiah: Journal of Islamic Studies, 2009)
This article presents Syed Muhammad Naquib Al-Attasâ opinion on the scope of Islam --a discourse that has become a hot issue among Muslim scholars since fourteen centuries ago and strongly reappeared along with the presence of a work of an orientalist, H.A.R. Gibb. According to Al-Attas, semantic approach is the best way to figure out whether Islam only touches upon religious matters or also includes a notion of civilization, because it is through this approach that the connotation of Islam will become clearer. As Islam is explicitly mentioned in the Quran as din, so the best way to identify the scope of Islam is to study the word-focus of din from semantic approach. From this approach, Al-Attas concludes that Islam as din includes the connotation of civilization, as the word din is closely related to the word madinah, a word that is also closely related to the word tamaddun (civilization). In addition to presenting Al-Attasâ ideas, the writer of this article also gives a critical remark on Al-Attasâ contention that din (religion) and dayn (debt) are closely related as the two words have the same root: dana. According to the writer, this opinion is not even supported by Quranic verses, which become the basis for Al- Attasâ semantic construction. Qurâan itself speaks of the two words, din and dayn, in clearly two different connotations.